Inventory Management Model for Batik Entrepreneurs in Laweyan Batik Village Based on Web Technology - Yenni Maria Sridarta; Dhian Kristantiningtyas; Yeremia Victor Rundonowu (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study analyzes the effectiveness and efficiency of implementing web-based technology in inventory management to support the sustainability of batik businesses in Kampung Batik Laweyan, Surakarta. Unlike companies that have good inventory records, batik entrepreneurs in this area still use manual records with demand-based production. This study uses a qualitative approach with a field study method to gain an in-depth understanding of the inventory management problems faced by batik entrepreneurs. Data collection was conducted through interviews and Focus Group Discussions (FGD). The results of the study indicate that inventory management is not optimal due to the absence of an effective control method. Purchases of raw materials are still based on estimates without careful planning, and there is no classification of inventory costs. The implementation of the EOQ (Economic Order Quantity) method has been shown to increase efficiency by determining the optimal order quantity and the right time to reorder. The implementation of a technology-based system has been shown to be more effective than manual records, with benefits such as increased data accuracy, operational efficiency, and reduced risk of recording errors. Overall, a technology-based system is an important strategy in increasing the competitiveness and sustainability of batik businesses in the digital era.